Reason for visiting the dentist following injury to permanent teeth among 12- 17-year-old-a retrospective study - GOPALASAMY, KIRTANA; GURUNATHAN, DEEPA; PRADEEP D (The journal of contemporary issues in business and government, 2020)
Traumatic injuries to permanent teeth in Pediatric patients must occur in the maxillary anterior tooth region and is one of the most common causes of visit to the dentist in emergency situations. Visiting the dentist following any trauma to the permanent teeth is of at most importance and their early management will help in managing any serious problems that may occur if left untreated. The retrospective study was conducted among patients who visited an institution in Chennai. The patients records were reviewed and the data of patients who visited between June 2019 to March 2020 were analysed. 2030 Pediatric patients who visited the dentist following traumatic injury to permanent teeth were included in the study. Retrospective analysis was done based on the collected data. Statistical analysis was performed in SPSS Software, data was analysed by descriptive and inferential statistics. 41.7% of patients reported with a chief complaint of fractured teeth. Males were most affected by traumatic injury (70.6%). The 12-17 years age group was most affected in the maxillary anterior region (55.90%). From this study we were able to conclude that fractured teeth was the most common chief complaint among patients reporting with traumatic injury and they complained of aesthetics being the most common concern. 12-17 years was the common age group affected by traumatic injury and the most component region to be affected was the maxillary anterior region. Males were most commonly associated with traumatic injuries then when compared to females. Patients with fractured teeth were the most common chief complaint and they visited the dentist within 1 year of the injury. It was seen that patients with ellis class 3 fracture was the most common traumatic injury and they visited the dentist within 1 year of the injury.